Association Abdominal Obesity with Dietary Habits and demographic Variables among Students at Southern Technical University - AbeerKhiryDekan,; JabbarTaresh Ahmed,; Sajjad Salim Issa, (University of Thi-Qar Journal of Science, 2023)
Obesity and overweight are still very common diseases affecting most regions of the world. According to studies, the increasing obesity prevalence in both adults and children of all ages, regardless of geography, race, or socioeconomic status. The Abdominal obesity is featured by fat accumulation in abdomen or atrophy of the large muscle group or both. So, the waist circumference (WC) is greater than the hip circumference (higher WHR) because of the accumulation of fat inside the abdomen. This study aims to find an association between abdominal obesity and dietary habits. Materials and methods: A cross-sectional survey; of 384 participants randomly selected from the formations of the Southern Technical University in Basra Governorate southern Iraq from (The College of Health and Medical Technologies, Technical College Administrative. Technical College of Engineering and Technical Institute in Basra) the data was gathered by conducting in-person interviews with the participants and utilizing thorough self-reporting survey questionnaires. Results: The present study reveals that more than half (51.0%) of students rest in the normal range. While 49.0% of them have abdominal obesity. Conclusion: With the exception of rice and soft drinks, the results of the current study showed no significant correlation between dietary habits and WC. To address the high incidence of abdominal obesity, among university students who need health education programs.